Crystal structure of N-(2-chlorophenyl)methoxycarbothioamide, C8H8ClNOS - Yeo, Chien Ing *; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C8H8ClNOS, triclinic, P¯1 (no. 2), a=6.7658(5) Å, b=8.0344(10) Å, c=9.6285(12) Å, α=66.279(12)°, β=72.245(9)°, γ=87.699(8)°, V =454.31(10) Å3, Z =2, Rgt(F)=0.056, wRref(F2)=0.158, T =100 K.